KONTRIBUSI MOTIVASI BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR SISWA SMK NEGERI 1 COT GIREK - Rinawati Samidi; Nelda Azhar (Universitas Negeri Padang, 2019)
The problem in this study is the level of success of students in participating in Graphic Design subjects that are still low under the value of the determination determined by the State Vocational School 1 Cot Girek. The minimum completeness criteria set by the school for Graphic Design subjects is 78. In reality in the field students who get <78 as much as 61.54% while those who get a value of ≥ 78 as much as 38.46%. The classification of achievement questionnaires for learning motivation variables was obtained as much as 78.32% which can be classified into classifications that have a strong category, classification of achievement questionnaires for learning environment variables obtained as much as 50.71% which can be classified into classifications which have sufficient categories, while for achievement classification questionnaire variable learning outcomes obtained as much as 81.14% which can be classified into classifications that have a strong category. The results of data analysis in this study are: The first hypothesis, tested based on regression tests simultaneously (together) using the F-Test. The second and third hypotheses were tested based on regression tests partially using the T-Test. Keywords: Contributions to learning motivation, contribution to the learning environment, learning outcomes.